PERLINDUNGAN HUKUM BERDASARKAN UNDANG-UNDANG NO. 30 TAHUN 2000 TENTANG RAHASIA DAGANG: Legal Protection Based on Law No. 30 Of 2000 Concerning Trade Secrets - Selly Olatersia Sembiring; Simona Bustani (Faculty of Law, Universitas Trisakti, 2024)
As one component of intellectual property rights, trade secrets have an important position in business activities in Indonesia. Problem formulation How well do the provisions of Law Number 30 of 2000 concerning Trade Secrets protect trade secret owners? And how reasonable is Law Number 30 of 2000 concerning Trade Secrets in interpreting judges' decisions No. 76/PDT.G/2021/PN.CKR on trade secret disputes the plastics industry? This research is analytical, descriptive, and is normative legal research. Deductive inference is used in qualitative analysis of existing evidence. The results and discussion indicate that Law Number 30 of 2000 on Trade Secrets is not yet adequate and effective in providing legal protection to trade secret holders due to its lack of relevance and many legal gaps. The judge ruled the case using Article 1365 of the Civil Code on Unlawful Acts, which is deemed inappropriate because the applicable law should be Law No. 30 of 2000 on Trade Secret Protection. The conclusion is Law No. 30/2000 on Trade Secrets, which provides legal protection to trade secrets in the plastics industry, is ineffective and inadequate in protecting trade secrets due to the absence of specificity regarding the scope, terms, legal protection, and sanctions of trade secrets